Children's fear and distress during a hospital-based family flu vaccine clinic: A parent survey. (March 2022) - Khadij, Sarah; Reszel, Jessica; Wilding, Jodi; Harrison, Denise
The aim of this study was to evaluate parents' perception of their child(ren)'s distress before, during, and after influenza (flu) vaccination, and their perceived effectiveness of pain and distress management strategies used during the vaccination process. This is a cross-sectional survey of parents attending Children's Hospital of Eastern Ontario's 2018 family flu clinic. After vaccination, parents completed a paper-based survey concerning demographics, fear and distress levels, and use and perceived effectiveness of pain/distress management interventions provided before and during the vaccination process. All survey data were entered into Research Electronic Data Capture (REDCap). Quantitative data were analyzed using descriptive statistics; qualitative data were analyzed using content analysis. A total of 164 parents completed the survey, reporting data on 327 children aged 6 months to 18 years (83% of children were vaccinated). Of 327 children, nearly half ( n = 142, 44%) were reported to be moderately to severely distressed before, during, or after the vaccination process. The parents reported that 268 (82%) children received pain/distress management strategies during vaccination. Over half ( n = 138, 57%) of the parents reported that the strategies used were very effective. Despite frequent use and parents' perceived effectiveness of pain/distress management interventions, nearly half of the children were perceived by parents as moderately to severely distressed during the vaccination process.